Two new species of Neosartorya from Brazilian soil - Horie, Yoshikazu (1995)
Among the isolates from soil of corn and sugar cane plantations in São Paulo State, Brazil, two new species of Neosartorya, IV. botucatensis and IV. paulistensis, are described and illustrated. Neosartorya botucatensis differs from the other known species of the genus in having ascospores with long spines on the convex walls. Neosartorya paulistensis is characterized by its ascospore walls with spinose and verruculose ornamentation. The former is compared with the closely related species IV. spinosa, and the latter is closely related to IV, glabra, IV. pseudofischeri and N, stramenia. © 1995, Mycological Society of Japan. All rights reserved.